2012
DOI: 10.1186/1752-1947-6-403
|View full text |Cite
|
Sign up to set email alerts
|

A prominent crista terminalis associated with atrial septal aneurysm that mimics right atrial mass leading to atrial arrhythmias: a case report

Abstract: IntroductionThe crista terminalis is a variant of normal anatomical structures within the right atrium that mimics an atrial mass on a transthoracic echocardiogram. Atrial septal aneurysm is a rare but well-recognized cardiac abnormality of uncertain clinical significance. The association between crista terminalis and atrial septal aneurysm is unusual but not completely casual. Both anatomical heart structures can lead to atrial arrhythmias.Case presentationThis case report describes the accidental discovery d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Atrial fibrillation is one of the most common SVAs observed in clinical practice . The relationship between ASAs and cardiac arrhythmias has been evaluated in various retrospective studies and case reports …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atrial fibrillation is one of the most common SVAs observed in clinical practice . The relationship between ASAs and cardiac arrhythmias has been evaluated in various retrospective studies and case reports …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluated the predictive role of intra鈥恖eft AEMD for paroxysmal atrial fibrillation recurrence after cardioversion, lone atrial fibrillation attack, new鈥恛nset AF after acute myocardial infarction, and occurrence of atrial arrhythmias in adult patients with congenital heart diseases . Few studies have evaluated the electrocardiographic and echocardiographic parameters reflecting heterogeneity of atrial depolarization in ASA patients, and only one previous study has analyzed the AEMD in healthy ASA population without interatrial shunt and the possible role of AEMD in early identifying SVAs in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During TEE examination, in particular, the mid-esophageal bicaval view may be the best way to visualize the crista terminalis (6,39). However, currently in the presence of an unclear cardiac mass on echocardiography, patients are usually referred to CMR for further evaluation (16)(17)(18). On CMR studies, the crista terminalis is described as the structure connected to the RA and the right atrial auricle, which has a similar signal intensity to the myocardium, and does not show enhancement after contrast injection (1).…”
Section: Discussionmentioning
confidence: 99%
“…It extends along the posterolateral aspect of the right atrial wall. Occasionally, this variant structure can become unusually prominent, consequently mimicking a right atrial mass 2. We report a case of a prominent crista terminalis recognised and properly diagnosed by cardiac MRI (CMR).…”
Section: Introductionmentioning
confidence: 97%